PERTUMBUHAN ANTHURIUM GELOMBANG CINTA (A. halmorei Croat) DAN ANTHURIUM BUNGA (A. andraeanum) PADA BEBERAPA FORMULA PUPUK - Yayuk Aneka Bety (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
The objective of the study was to find out the respons of A. andraeanum and A. wave of love   to various fertilizer formula. The experiment was carried out on April 2007 to April 2008 in the plastic house in Segoro gunung, Karang anyar.  The experiment was arranged in a factorial design, with three replications.  The first factor was species of Anthuriums (A. andraeanum and   A. Wave of love), and the second factor was fertilizer formula.  The fertilizer used were granule slow release fertilizer (chemical fertilizer), green brown liquid fertilizer (organic), light green crystallic fertilizer (chemical), and green liquid fertilizer (organic). Plant height and number of leaves were measured at 6, 8, 10, and 12 months after planting, and flower number, flower stalk length, spathe length, spathe width, and spadix length were measured at 12 month after planting.  The results of the experiment showed that A. andraeanum dan A. Wave of love had different response to the fertilizer formula. Light green crystallic fertilizer, slow release fertilizer, and liquid green brown fertilizer were suitable for the vegetative growth of A. andraeanum, while only light green crystallic fertilizer and slow release fertilizer were proper to the vegetative growth of          A. Wave of love.  The generative growth of A. andraeanum was better in the application of light green crystallic fertilizer, and slow release fertilizer.